MENCIPTAKAN MASYARAKAT SEHAT DI PUSKESMAS CIKUPA, TANGERANG - Atzmardina, Zita; Natalie, Michelle Ruth; Yusliani, Cindy; Seong, Marcus Wong Kit; Susanto, Devy Fransiska (Jurnal Serina Abdimas, 2024)
Creating a healthy society is very important to maintain the continuity of life. Maintaining health aims to prevent the spread of infectious diseases. One of the infectious diseases is Tuberculosis (TB). To date, Indonesia is ranked second in terms of TB cases in the world with a total of 969 thousand cases or around 1 new case every 33 seconds. Based on the 2023 SKI Report, Banten province ranks 3rd in the province with the most TB cases in Indonesia after Papua and West Java. The number of TB cases at the Cikupa Community Health Center in 2023 will be 192 cases. The aim of this activity is to increase public knowledge in creating healthy behavior so that the number of people suffering from disease, especially infectious diseases, can be reduced. The method uses the Blum Paradigm to identify the cause of the problem, a mini-survey to collect data, the Delphi non-scoring method to determine problem priorities, and a fishbone diagram to determine the root cause of the problem. Activities carried out include counseling and demonstrations on cough etiquette, CTPS, and use of masks. Intervention activities are monitored using the Plan-Do-Check-Action (PDCA) cycle and a systems approach for evaluation. Based on the Delphi non-scoring method, it was found that lifestyle factors were priority problems that had to be resolved immediately. The results of the intervention showed that 26 participants (72.22%) met indicators 1 and 2 and 5 participants who were called randomly were able to practice demonstrations of cough etiquette, CTPS and the correct use of masks. From this activity, it can be seen that there is an increase in knowledge so that it is hoped that it can reduce cases in the Cikupa Health Center working area. ABSTRAK Menciptakan masyarakat yang sehat sangat penting bagi menjaga keberlangsungan hidup. Menjaga kesehatan bertujuan mencegah terjangkitnya penyakit menular. Salah satu penyakit menular yaitu Tuberkulosis (TB). Hingga saat ini, Indonesia menempati peringkat kedua kasus TB tertinggi di dunia dengan jumlah kasus sebanyak 969 ribu atau sekitar 1 kasus baru setiap 33 detik. Berdasarkan Laporan SKI tahun 2023, propinsi Banten menempati urutan ke-3 provinsi dengan kasus TB terbanyak di Indonesia setelah Papua dan Jawa Barat. Jumlah kasus TB di Puskesmas Cikupa tahun 2023 sebesar 192 kasus. Tujuan dari dilakukannya kegiatan ini adalah untuk meningkatkan pengetahuan masyarakat dalam menciptakan perilaku sehat sehingga dapat diturunkannya jumlah masyarakat yang menderita penyakit, khususnya penyakit menular. Metode menggunakan Paradigma Blum untuk mengidentifikasi penyebab masalah, mini-survey untuk mengumpulkan data, metode non-scoring Delphi untuk menentukan prioritas masalah, serta diagram fishbone untuk menentukan akar penyebab masalah. Kegiatan yang dilakukan mencakup penyuluhan serta demonstrasi etika batuk, CTPS, dan penggunaan masker. Kegiatan intervensi dimonitoring dengan Plan-Do-Check-Action (PDCA) cycle serta pendekatan sistem untuk evaluasi. Berdasarkan metode non-scoring Delphi, diperoleh faktor lifestyle menjadi prioritas masalah yang harus segera diselesaikan. Hasil intervensi menunjukkan sebanyak 26 peserta (72,22%) memenuhi indikator 1 dan 2 serta 5 peserta yang dipanggil secara acak dapat mempraktikkan demonstrasi etika batuk, CTPS, dan penggunaan masker dengan benar. Dari kegiatan ini bisa dilihat adanya peningkatan pengetahuan sehingga diharapkan dapat menurunkan kasus di wilayah kerja Puskesmas Cikupa.